2011
DOI: 10.1002/smr.563
|View full text |Cite
|
Sign up to set email alerts
|

An evidence‐based model of distributed software development project management: results from a systematic mapping study

Abstract: Distributed software development (DSD) has intensified over the past few years, and DSD project management is more complex than collocated project management. However, no systematic research effort has focused on aggregating evidence from the scientific literature to build models to support project management on DSD context. For these reasons, the goal of this paper is to build an evidence-based model of DSD project management from the research findings about challenges of DSD and the practices, models and too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Jalali et al [13] and Hossain et al [14] performed systematic literature reviews looking at the use of agile methods in GSD. Da Silva et al performed two SLRs on project management in the context of GSD [15], [16]. Prikladnicki et al [17] identified papers that describe process models for GSD in the context of overseas outsourcing.…”
Section: Introductionmentioning
confidence: 99%
“…Jalali et al [13] and Hossain et al [14] performed systematic literature reviews looking at the use of agile methods in GSD. Da Silva et al performed two SLRs on project management in the context of GSD [15], [16]. Prikladnicki et al [17] identified papers that describe process models for GSD in the context of overseas outsourcing.…”
Section: Introductionmentioning
confidence: 99%
“…Such a well-defined work package structure promises to ease work transfer between locations and to achieve low dependencies between locations during actual implementation work [7,8,12,14,20,26,[36][37][38][39][40][41]. This way it might be possible to reduce communication and coordination needs between di↵erent locations.…”
Section: Product Structurementioning
confidence: 99%
“…In the case of the O↵shore insourcing scenario that has peer-to-peer close partnership orientation, it could be suitable to establish standardized guidelines for a common software development process and tools between sites. This promises to create a joint corporate level of work standards [7,37,43]. …”
Section: Development Processmentioning
confidence: 99%
See 1 more Smart Citation
“…SM aims to provide high-level analysis of relevant research literature by classifying the work according to a series of defined categories and visualizing the status of a particular field of research (Mohd Fauzi et al, 2010, Petersen et al, 2008. This technique has been used recently in the GSE field (Steinmacher et al, 2012, Jalali and Wohlin, 2010, da Silva et al, 2011, Mohd Fauzi et al, 2010, Portillo-Rodríguez et al, 2012. In these studies specific aspects of GSE research were categorized (using guidelines presented in Charters, 2007, Petersen et al, 2008)).…”
Section: Introductionmentioning
confidence: 99%